Effectiviness of Disaster Education in Early Childhood Education in Magelang Regency - Rahmawati, Siti Azizah (Prosiding University Research Colloquium, 2021)
The study aims to know the application of Disaster Education at the institutions studies especially in disaster prone areas. The type of research take a descriptive qualitative study through observation, interviews and analizing document as a method of collecting data. The collected data were analyzed using Miles and Huberman techniques, through data reduction, display data, and a deduction. The Research took place in RA muslimat nu 1 wonolelo village sawangan district magelang regency. This research took this place due to has a high risk of Merapi volcanoes that range 5-7 km to the summit of the flaming mountain. The results of the Research indicates: 1) the mechanism of the disaster education management in ra muslimat nu 1 wonolelo hasn't been carried out in accordance with the disaster educational guidelines. The institution has not established themselves as one of the disaster education developers in the curriculum. 2) the material of disaster education presented is a set of points that are considered important, while handling children's reactions was only by giving understanding and giving children a sense of secure. 3) the implementation of the integration Disaster Education in the curriculum and learning plan documents as well as an assessment of Disaster Education had not been carried out. 4) The inhibiting factors for the implementation of disaster education include learning media is still a bit . The effectiveness of disaster education has not been carried out effectively, but in this research indicates that the institution has been an effort to apply disaster education in every learning activities.